DEVELOPMENT OF GOOGLE SITES MEDIA TO IMPROVE STUDENTS' LEARNING INTEREST IN THE IMPORTANCE OF HAVING SYAJA'AH CHARACTERISTICS AT MAN PEMATANG SIANTAR - Sirait, Azyana Alda; Nasution, Indah Widya Jaya Putri; Siregar, Muhammad Irfansyah; Halimaini K, Putri; Ilfah, Ade; Nasution, Wahyuddin Nur (Reflektika, 2025)
This research aims to develop learning media based on Google Sites to increase students' interest in learning, especially in the material "The Importance of Having Shaja'ah Characteristics" at MAN Pematangsiantar. The research method used is Research and Development (R&D) with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The research results show that the use of Google Sites significantly increases students' interest in learning, which is reflected in positive student responses, increased participation during learning, and better evaluation results compared to conventional methods. The intuitive display and interactive features on Google Sites encourage active student involvement and make it easier to understand the values of honesty and courage according to Islamic teachings. This research concludes that Google Sites media is an effective and relevant learning tool in the digital era, with the support of technical guidance from teachers and parents to ensure its success.